Stabilization of Nanostructured-oriented CaCuO2 Thin Films: A Descriptive Study - Anita Bagri; A. Wadikar; Rakesh Kumar Shah; R. J. Choudhary; D. M. Phase (New Trends in Physical Science Research Vol. 1, 2022)
The present study highlights the growth nature of CCO films on these two substrates which offer different strain caused due to lattice mismatch between the chosen substrate and CCO. Using a pulsed laser deposition technique, nanostructured c-axis oriented thin films of CaCuO2 were grown on single crystalline (110) NdGaO3 and (100) LaAlO3 substrates. The structural characterization reveals that the grown CaCuO2 films are single phase and oriented (00l) on both substrates. The stoichiometric growth of the film is ensured by an energy dispersive X-ray spectroscopic study. Scanning electron microscopy confirms the nanostructured morphology of the CCO film. The island growth is responsible for the nanostructured c-oriented thin film as observed in the SEM images. These nanostructured CCO film can be good candidate for the thermoelectric materials.